PEMBANGUNAN BERKELANJUTAN DALAM PEMBENTUKAN HUKUM LINGKUNGAN - kambey, Trifena Julia; Rumayar, Gerrard Wayne; Lumintang, Gabriel Imanuel; Yakob, Rafanli (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Sustainable development is a fundamental principle that guides economic, social, and environmental policies in Indonesia. This study aims to analyze the integration of sustainable development principles within the national environmental law system, particularly in the context of risk-based licensing reforms following the enactment of the Job Creation Law and Government Regulation No. 22 of 2021. This research employs a normative juridical approach, combining statute, conceptual, and case approaches, supported by primary legal materials (laws and court decisions) and secondary sources (academic literature and institutional reports). The analysis was conducted qualitatively through a deductive syllogism method and grammatical, systematic, and teleological interpretation to assess the coherence between legal norms and sustainability principles. The findings indicate that although the principles of precaution, state responsibility, public participation, and polluter pay have been incorporated into Indonesia’s environmental law framework, their implementation remains formalistic and ineffective in mitigating the environmental impacts of development. The risk-based licensing regime enhances administrative efficiency but potentially weakens preventive oversight mechanisms and public transparency. Institutional weaknesses, fragmented central–local authority, and the limited use of economic instruments further constrain legal effectiveness. This study emphasizes the need for legal reform through the strengthening of strategic environmental assessment, integration of digital monitoring systems, and substantive application of the polluter pays principle. The results contribute to the advancement of ecological constitutionalism and sustainable governance frameworks within developing countries, providing practical implications for the reform of environmental legal policies toward a more equitable and sustainable development paradigm.